Agile method of development of learning objects for engineering (MADOA) - Huamaní, Gloria (2014)
The aim of this article is to show an agile method for developing learning objects for Engineering applied to the simulation course, being a related topic any engineer, has allowed us to obtain 7 learning objects that could be reused for different courses and specialties.